Impact of Physiotherapy on Quality of Life and Arm Function after Breast Cancer Surgery in Women of Different Age - Aušra Tvarijonavičienė (Lithuanian Sports University, 2020)
Breast cancer is the most common oncological disease among women. After breast cancer surgery women face various physical and psychosocial problems. They often suffer from arm lymphedema, poor posture, and pain. Side effects of breast cancer surgery can greatly affect general physical health and quality of life. To manage the problems it is necessary to apply rehabilitation. The most important part of rehabilitation is physiotherapy with the main aim of helping patients to recover and to achieve their maximum functional level (Hsieh et al., 2008). The aim of this study was to determine the impact of physiotherapy on differently aged women's arm function after breast cancer surgery. The sample size of the survey was 40 women who were referred for post operative outpatient rehabilitation. The participants were divided into two age groups: I group - women aged 35-49 years (n = 20, average age 42 ± 4.30 yrs.); II group - women aged 50-64 years (n = 20, average age 56 ± 5.39 yrs.). Shoulder range of motion, arm circumference and pain were measured before and after 14 physiotherapy procedures, their general health state and quality of life were assessed as well. Shoulder range of motion increased, arm swelling and pain on the operated side decreased significantly in women of different age. General health status and quality of life after physiotherapy improved significantly both in younger and older women, but there were no significant differences between groups. After breast cancer surgery more than half of the women had psychological problems and were worried about their health in future, and less than half experienced body image problems and faced various social problems. Physical therapy was equally effective for both younger and older women. Keywords: physiotherapy, breast cancer, lymphedema, quality of life.